2015
DOI: 10.1080/23294515.2014.998351
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Pediatric Ethics: Results of a Survey of Pediatric Ethics Consultants

Abstract: Background: Ethics consultants (ECs) are increasingly expected to possess core knowledge and skills. Few data address whether ECs actually possess recommended core knowledge. We aimed to measure pediatric ECs' understanding of ethical principles, identify knowledge gaps, and explore associations between experience/training and knowledge in pediatric ethics consultations. Methods: We identified the 2 ECs most knowledgeable in pediatric ethics from each of 45 freestanding children's hospitals and an equal number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Furthermore, the current results of the study showed that most participants supported the need for education in clinical research ethics and preferred faceto-face learning modules to distance learning courses. Further education in clinical research ethics would improve investigators' performance in ethics knowledge tests [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the current results of the study showed that most participants supported the need for education in clinical research ethics and preferred faceto-face learning modules to distance learning courses. Further education in clinical research ethics would improve investigators' performance in ethics knowledge tests [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%